2023
DOI: 10.1021/acs.est.2c08548
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Drinking Water Manganese Concentrations in Domestic Wells and Community Water Systems in the Central Valley, CA, USA

Abstract: Over 1.3 million Californians rely on unmonitored domestic wells. Existing probability estimates of groundwater Mn concentrations, population estimates, and sociodemographic data were integrated with spatial data delineating domestic well communities (DWCs) to predict the probability of high Mn concentrations in extracted groundwater within DWCs in California’s Central Valley. Additional Mn concentration data of water delivered by community water systems (CWSs) were used to estimate Mn in public water supply. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…Additionally, we found a higher percentage of very small system users (14.2%) potentially exposed to Mn concentrations exceeding the WHO guideline value at point-of-entry than very large systems (2.1%, Table ). Previous analyses of primary contaminant violation in community water systems have also reported higher instances of primary contaminant violations in smaller systems and have attributed this difference to difficulty in accessing treatment options. ,, Larger systems have better economy-of-scale and can easily distribute management and treatment costs across a large user base. In contrast, since small systems serve less users, the costs of additional treatment may no longer meet user affordability requirements. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found a higher percentage of very small system users (14.2%) potentially exposed to Mn concentrations exceeding the WHO guideline value at point-of-entry than very large systems (2.1%, Table ). Previous analyses of primary contaminant violation in community water systems have also reported higher instances of primary contaminant violations in smaller systems and have attributed this difference to difficulty in accessing treatment options. ,, Larger systems have better economy-of-scale and can easily distribute management and treatment costs across a large user base. In contrast, since small systems serve less users, the costs of additional treatment may no longer meet user affordability requirements. …”
Section: Discussionmentioning
confidence: 99%
“…Since these systems lack regular reporting or treatment, raw groundwater chemistry is more likely representative of the composition at tap. In the previous analysis, Mn in groundwater accessed by domestic well communities and reported water quality in CWSs in California’s Central Valley, more domestic well users (0.4%) then community well users (0.05%) were accessing Mn concentrations exceeding the 300 μg L –1 health-advisory limit . Further analysis of Mn concentrations in domestic versus public wells throughout the United States, McMahon et al observed more Mn concentrations exceeding the 300 μg L –1 health-advisory limit in domestic wells (7.2%) than public wells (5.2%) due to the impact of land surface-soil-aquifer connections on Mn release and well depth.…”
Section: Data Limitationsmentioning
confidence: 94%
“…Rather, several studies have reported reductive transformations of birnessite (Mn­(IV) oxide) to Mn­(III)­OOH, or mixed-valent Mn­(II,III) 3 O 4 , while in the presence of aqueous Mn­(II), which lowers the overall redox buffering capacity. ,, Additionally, Mn­(II) can passivate reactive surface sites, block sorption sites on AC, or occupy vacancy sites on Mn oxide that can decrease total sorption capacity. ,, Reactions between Mn­(III) or (IV) oxides and electron donors such as sulfide minerals or organic matter can cause reductive dissolution and generate high concentrations of aqueous Mn­(II) . There is increasing concern about Mn contamination of drinking water, which can lead to neurotoxic health effects. , Precipitation of Mn­(II) compounds such as rhodochrosite (MnCO 3 ), or oxidation to Mn­(III) or Mn­(III,IV) solids, may limit the concentration of Mn­(II) in solution, but these processes can be kinetically slow and are strongly pH dependent. , Oxidation of Mn­(II) can be catalyzed both abiotically through complexation with organic compounds or by Mn­(IV) oxide mineral surfaces and biotically through various enzymatically driven bacterial or fungal pathways. , Calcareous systems such as EFPC can promote the stability of Mn­(II) solids, and the presence of additional electron acceptors (e.g., nitrate) can potentially reoxidize Mn­(II) to provide additional redox buffering …”
Section: Discussionmentioning
confidence: 99%
“…13 There is increasing concern about Mn contamination of drinking water, which can lead to neurotoxic health effects. 93,94 Precipitation of Mn(II) compounds such as rhodochrosite (MnCO 3 ), or oxidation to Mn(III) or Mn(III,IV) solids, may limit the concentration of Mn(II) in solution, but these processes can be kinetically slow and are strongly pH dependent. 95,96 Oxidation of Mn(II) can be catalyzed both abiotically through complexation with organic compounds or by Mn(IV) oxide mineral surfaces and biotically through various enzymatically driven bacterial or fungal pathways.…”
Section: + 2mn(iii)mentioning
confidence: 99%
“…As reviewed by Johnson and Belitz (2015) and London et al (2021), rural areas or outside of incorporated city boundaries are less likely to be served by municipal or other larger public water supply systems. Consequently, rural areas heavily depend on private domestic wells for their water supply, which significantly increases their risks of water shortages and compromise their water quality (Balazs and Ray 2014, Horowitz et al 2016, Tariq and Naughton 2021, Pace et al 2022, Aiken et al 2023, Hauptman et al 2023.…”
Section: Social Impactsmentioning
confidence: 99%